Designing Wayang Kulit Purwa with Gatotkaca as the Character in Game - Nunnun Bonafix (Journal of Games, Game Art, and Gamification, 2017)
Young generation nowadays has lack of knowledge on the culture of shadow puppet (wayang kulit) which is a heritage that has a high value of art and philosophy. This is caused by the impact of foreign cultures rapidly entering Indonesia. The rapid development of the information technology through internet & game has led to globalization that seems to be not limited to space and time. The speed of information and foreign cultures cannot be stopped. The culture of shadow puppet (wayang kulit) is getting eroded and is not much known by the modern society nowadays. This is an irony to a big nation which has a rich heritage, so it is our obligation as a citizen to maintain and preserve it. Based on the formulae of AIGA 2015 that defines (time + content + context) / time = experience design, the game of wayang kulit (shadow puppet) Gatotkaca put forbattled different experience to users in exploring the information and entertainment in those media. Having the spirit of moderate Postmodernism, the design plan called User Interface which combines the modern and classic traditional elements will encourage new experience to the users (Experience Design). The design recognizes times and trends, and it keeps changing as the development of the times. The design can be a pace setter to next individuals who are called to maintain and preserve national cultures, in general, and wayang kulit purwa, in particular, through digital media. The development in the modern era will not change the identity of shadow puppet (wayang kulit) culture since it has solid foundation.